MAKNA HIDUP: TINJAUAN DARI KITAB PENGKHOTBAH PASAL 1 DAN 2 - Steven Mallisa'; R. Nimba Malosang (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
ABSTRACT: The meaning of life: a review of Ecclesiastes chapters 1 and 2. The meaning of life is a profound question that has stirred the human heart since ancient times. In the Book of Ecclesiastes chapters 1 and 2, this question is answered with honesty and sharp reflection on human experiences pursuing wisdom, pleasure, hard work, and wealth—yet ultimately concluding that all is vanity. The Hebrew word hebel, meaning “vapor,” becomes a symbol of the fleeting and uncertain nature of everything in the world. This journal employs a qualitative method with a theological-reflective approach to explore the contents of Ecclesiastes and connect it with the existential condition of modern humans who often feel emptiness amid abundance. Through biblical text analysis and spiritual reflection, it is found that the true meaning of life does not lie in worldly, temporary things, but in a life centered on God. Only in a right relationship with God can humans find true satisfaction, joy, and purpose in life.